GPER Function in Breast Cancer: An Overview - Lappano, Rosamaria; Pisano, Assunta; Maggiolini, Marcello (Frontiers in Endocrinology, 2014)
The G-protein-coupled estrogen receptor 1 (GPER, formerly known as GPR30) has attracted increasing interest considering its ability to mediate estrogenic signaling in different cell types, including the hormone-sensitive tumors like breast cancer. As observed for other GPCR-mediated responses, the activation of the epidermal growth factor receptor (EGFR) is a fundamental integration point in the biological action triggered by GPER. A wide number of natural and synthetic compounds, including estrogens and antiestrogens, elicits stimulatory effects in breast cancer through GPER up-regulation and activation, suggesting that GPER function is associated with breast tumor progression and tamoxifen resistance. GPER has been also proposed as a candidate biomarker in triple negative breast cancer, opening a novel scenario for a more comprehensive assessment of breast tumor patients.